Report on the Progress of Comment Programmes in the Uttar Pradesh 1950 - Planning Commission (Planning Commission, 1950)
The purpose of this report is to provide a base-line from which the consideration of future development schemes of the State can be made. The Government of the Uttar Pradesh have always kept before them the objective of providing to the people the basic essentials of life — food, cloth, shelter, education, and medical facilities. Their concern for improving the life and happiness of the citizen of the Stale is clearly reflected in the fact that while the provision for expenditure on civil administration Services rose from Its. 7-3 crores in 1 945-4(I to Rs. 1-1-2 crores in 194S1-50, the development expenditure budgeted for the current financial year is of the order of Rs. 19-9(1 crores against Rs. crores in 1945-41. the year before the present Government took over the reins of administration. Besides, the capital expenditure on Irrigation and Hydel work alone, which was only Rs. 1-5 crores in 1945-49 is now Rs. 4-7 crores in 1950-51.
Government of Uttar Pradesh